Bogdan Walczak jako znawca twórczości Henryka Sienkiewicza - Mariak, Leonarda (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
This paper contains an overview of all the works about Sienkiewicz’s output written by Professor Bogdan Walczak. It includes the critical review of the scientific achievements of the Poznań-based researcher, which revealed the features of both the researcher’s scientific workshop and the work of the Polish Nobel Prize winner. Walczak’s scientific interests concerned mainly the linguistic and stylistic development of Sienkiewicz’s most important novels. Thanks to the researcher’s works, knowledge about the Trilogy, On the Field of Glory and Quo Vadis has been expanded and updated. The Professor is among the narrow group of the most outstanding experts on the Polish Nobel Prize winner’s work and is an undisputed authority in this field.